1972
DOI: 10.1037/h0032322
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of the contrast effect and its implications for intergroup communication and the indirect assessment of attitude.

Abstract: Experiments I and II were designed to differentiate between alternative interpretations of the contrast effect. Experiment I examines and rejects the hypothesis that the effect is specific to rating scales, since the effect also occurs when subjects are asked to make CDmparative judgments. Experiment II leads to the rejection of the hypothesis that the effect is purely semantic (i.e., specific to situations in which verbal labels are applied to attitudes); when subjects are asked to write items that would be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 20 publications
1
70
0
1
Order By: Relevance
“…To examine the moral stereotypes that liberals and conservatives hold about each other, we took advantage of a method introduced by Dawes, Singer, and Lemons [23] of having partisans indicate the values of “typical” partisan group members, allowing comparison of these projections with the partisans' actual answers. Participants completed multiple versions of the Moral Foundations Questionnaire (MFQ; [16]).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the moral stereotypes that liberals and conservatives hold about each other, we took advantage of a method introduced by Dawes, Singer, and Lemons [23] of having partisans indicate the values of “typical” partisan group members, allowing comparison of these projections with the partisans' actual answers. Participants completed multiple versions of the Moral Foundations Questionnaire (MFQ; [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported strong accentuation or contrast effects with ideologically opposed groups (e.g., Dawes et al, 1972), and with groups expressing a clear preference for ingroup over outgroup (Clarke & Campbell, 1955;Judd et al, 1991). The present research asked whether comparable accentuation effects would be observed in a context where ingroup favoritism was minimal or absent, and also whether accentuation effects were dependent on real differences between groups.…”
Section: Discussionmentioning
confidence: 77%
“…In the Dawes et al (1972) research, for example, the campus sample of Hawks and Doves was a very small sample of the larger population of Hawks and Doves nationwide, and it is possible that the university sample was not typical of the population. More generally, when subjects are asked to make judgments about a population, it is important to consider the size and/or representativeness of the sample used to infer population characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…The finding that three revised images produced a higher average score before drinking than after drinking is attributed to a high expectation resulting in lower satisfaction [26]. That is, the average after drinking was lower because the desire to drink was initially high.…”
Section: Desire To Drinkmentioning
confidence: 79%